2008
DOI: 10.5271/sjweh.1167
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence among Finnish farmers, 1995–2005

Abstract: Objectives The aim of this study was to describe the cancer risk pattern of male and female Finnish farmers and to define the role of the type of farm production as a risk determinant.Methods All farmers on 31 December 1978 living on 1 January 1995 were included in the cohort. The data concerning continuation as a farmer and the type of farming was collected from the 31 December 1990 and 1994 farm registries. The observed number of cases in each stratum was divided by the respective expected number based on na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
2
43
2
Order By: Relevance
“…As a result, individuals employed in agriculture tend to experience lower overall morbidity and mortality compared to the general population, and also exhibit distinctive cancer risk profiles [14]. Studies of cancer incidence and mortality in farmers have consistently reported reduced risks of tobacco-related cancers, such as lung and bladder [2, 3, 57]. Lower incidence of colorectal cancer has also been attributed to this favourable risk factor profile that includes higher levels of physical activity [3, 5, 7–9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, individuals employed in agriculture tend to experience lower overall morbidity and mortality compared to the general population, and also exhibit distinctive cancer risk profiles [14]. Studies of cancer incidence and mortality in farmers have consistently reported reduced risks of tobacco-related cancers, such as lung and bladder [2, 3, 57]. Lower incidence of colorectal cancer has also been attributed to this favourable risk factor profile that includes higher levels of physical activity [3, 5, 7–9].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of apparent protection is related to the intensity of the exposure (the number of cattle to which the farmers were exposed) but wanes when the farmers change to other occupations. These findings were confirmed in a high-quality study in Finland [49], and in a meta-analysis of published reports [50]. Although it has been claimed that the agents conferring protection are endotoxins that are present in the dust derived from cattle faeces [51], it is equally likely that apparent protection is mediated by various genera and species of actinomycetes, which are likewise present, and at high densities, in cowsheds.…”
Section: Introductionmentioning
confidence: 72%
“…A recent study of the Finnish farmers including all farmers in the national farm register revealed that the overall standardised incidence ratio among farmers was significantly reduced, and for most cancers, the incidence was below 1.0 [25]. Concordant results were recently obtained for Italian farmers [26].…”
Section: Microbes and Cancermentioning
confidence: 82%
“…Accumulating data obtained from several lines of evidence suggest that cancers occur less frequently 1. Among people who are, by occupation, heavily exposed to environmental micro-organisms [25][26][27][28][29][30][31][32][33] 2. Among populations that adhere to a traditional lifestyle [34] 3.…”
Section: Microbes and Cancermentioning
confidence: 99%